2007
DOI: 10.1002/mrd.20684
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptors α and β in the corpus luteum and uterus from non‐pregnant and pregnant llamas

Abstract: Because estrogen may be involved in maternal recognition of pregnancy and embryonic migration in llamas, expression of estrogen receptor subtypes alpha (ERalpha) and beta (ERbeta) was evaluated in corpus luteum (CL), endometrium, and uterus using relative RT-PCR. Tissues were recovered from sterile-mated (SM) and pregnant (PG) females during Days 7-11 and 7-13 (Day 0 = day of mating), respectively, and follicular phase and juvenile females. Luteal expression of ERalpha and beta was similar (P > 0.10) in SM and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
(52 reference statements)
3
11
0
Order By: Relevance
“…Because all embryos migrate to the left horn, a greater expression of ER in the right horn to promote its contraction was expected but could not be demonstrated. This suggests that a more complex mechanism with differential expression of ER subtypes may be involved in embryo migration from the right to the left horn (Powell et al, 2007a). These findings were supported by recent work in our laboratory, which did not demonstrate a greater expression of ERα in the right uterine horn of pregnant alpacas (Figure 4 and 5) to promote its contraction (Campbell, 2015), as well as recent research performed in camels (Abdoon et al, 2017).…”
Section: Maternal Recognition Of Pregnancy In Camelidssupporting
confidence: 82%
See 1 more Smart Citation
“…Because all embryos migrate to the left horn, a greater expression of ER in the right horn to promote its contraction was expected but could not be demonstrated. This suggests that a more complex mechanism with differential expression of ER subtypes may be involved in embryo migration from the right to the left horn (Powell et al, 2007a). These findings were supported by recent work in our laboratory, which did not demonstrate a greater expression of ERα in the right uterine horn of pregnant alpacas (Figure 4 and 5) to promote its contraction (Campbell, 2015), as well as recent research performed in camels (Abdoon et al, 2017).…”
Section: Maternal Recognition Of Pregnancy In Camelidssupporting
confidence: 82%
“…The authors suggested that the presence of an embryo may be influencing this expression (Powell et al, 2007a). Endometrial expression of ERα and ERβ was not affected by uterine side or days post-mating.…”
Section: Maternal Recognition Of Pregnancy In Camelidsmentioning
confidence: 99%
“…2001). Previous reports have shown an absence of ERβ RNAm during the follicular phase in llamas (Powell et al. 2007).…”
Section: Discussionmentioning
confidence: 74%
“…E2 is well accepted to be a critical component of endometrial development and pregnancy in both animal and human models [13,15]. Some studies have shown that, in some women, E2 levels may drop during the luteal phase of an IVF cycle [14].…”
Section: Resultsmentioning
confidence: 99%
“…Animal and human studies have shown that estradiol (E2) serves a critical role in endometrial development compatible with successful pregnancy [13,14]. Additionally, data have shown that, in some women, E2 levels fall in the mid luteal phase of an IVF cycle [14].…”
Section: Introductionmentioning
confidence: 99%